The Political Morphology of Drainage—How Gully Formation Links to State Formation in the Choke Mountains of Ethiopia. (October 2017) - Smit, Hermen; Muche, Rahel; Ahlers, Rhodante; van der Zaag, Pieter
Highlights: A morphological reading of Ethiopia's "developmental state" program is proposed. This shows how drainage and soil conservation practices are historically configured. This reveals how objects take part in the power relations that shape land degradation. This reveals how local agents involve in shaping the "developmental state". Summary: To understand why soil erosion is persistent despite three decades of massive investments in soil conservation, this paper explores how drainage and soil conservation change a hill slope in the Choke Mountains. By paying close attention to the practices that reshape the hill, we account for the active roles of people and material flows in shaping their identities, forms, and power relations. Social relations can be read in the landscape as their material outcomes are literally scoured into the hill slope. Such a material reading of Ethiopia's "developmental state" reveals three issues: First, drainage and soil conservation practices are configured by particular historical regimes of land distribution and rent appropriation. Second, the power of the Ethiopian government's model of the developmental state derives from the exploitation of this configuration by a new coalition of landholders and government officials. Government officials mobilize landholders to construct terraces in exchange for government support in conflicts over land and input distribution. When the terraces create obstructions that can trigger flooding, landowners convert them into drains and divert drainage flows to plots sharecropped by landless families. Consequently, the yearly mobilization for terrace construction does not halt soil erosion but further aggravates it. This continues because the performance of this yearly ritual affirms the authority of landholders and government agents. Third, landless families which fail to live up to the model of the "farmer interested in soil conservation" have created a competing "trader model" with its own institutions. The denial of their non-farmer identities by landholders and officials fuels generational conflicts over drainage which deepen the fractures in the hill and pose a challenge to government authority. Land degradation thus embodies both the powers and the limits of the developmental state.